(untitled) (Journal of Health Sciences, 2023)
Introduction: information and communication technology (ICT) has multiplied its availability and use, resulting in enormous usage, especially among school-age children, who use it for an average of 7.5 hours per day. The amount of time adolescents spend in front of electronic screens has increased significantly between the ages of 10 and 14, but there are significant gender changes. For boys, this increase is 41.6 minutes per day, while for girls it is 22.7 minutes per day. Methods: The study is designed as an epidemiological, cross-sectional, descriptive-analytic, comparative study. The study will be conducted in the form of an online questionnaire on the Microsoft Forums platform during the period 12/15/2021 to 12/30/2021. Respondents were able to access the request for consent using a link and a QR code, which was previously signed by a parent/guardian giving consent for children to participate in this study. Results: The results of this study show that school-aged children generally use cell phones with a touch screen between 2 and 3 hours daily during the work week (39.2%) and TV (39.5%). Pain caused by ICT use in the past 12 months occurred mainly in the neck/shoulder area (42.4%), while pain in the previous month occurred mainly in the lower extremities (29.1%). Conclusion: Increased use of ICT devices was associated with higher levels of musculoskeletal symptoms. The higher pain burden in various body parts is of concern, and further research on the effects of ICT device use in adolescents is needed and warranted.